Prilagojenost socialnovarstvenih oblik pomoči starim ljudem v Mestni občini Ljubljana - Breznik, Danuška (Socialno delo, 2015)
In Slovenia, the services offered to the elderly and provided by both public and private sectors do not meet the needs of a heterogeneous population of the older people and do not enable them to have good quality of life in their old age. The quality of life of the elderly in Slovenia is largely influenced by forms of assistance for the older people, intergenerational solidarity, and the financial situation of the elderly. The results of the research "Assessment of the needs of older people in the Municipality of Ljubljana" indicate that the forms of social security assistance for older people are basically financially unattainable for the majority of respondents. Sometimes relatives as a source of social support - especially children - need to help their parents covering the cost of the most basic needs. Personalized environment and increased access to services are two basic requirements that can improve the quality of everyday life. The task of social workers is to adjust help to the needs of the older people and to research their life-world. Therefore social workers should take into consideration older people's heterogeneous needs, and respond with the individualized approach based on the user perspective and the concept of rights, where the users have influence over the design of their service.
Keywords: intergenerational solidarity; social work; socialno delo; medgeneracijska solidarnost; rights; social welfare; stari ljudje; assistance; potrebe; pravice; quality agenig; needs of the elderly; socialnovarstvene storitve; kakovostna starost